2018
DOI: 10.1002/ps.5189
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the EU neonicotinoid seed‐dressing ban on oilseed rape production in England

Abstract: Increasing resistance to pyrethroid insecticides in combination with the neonicotinoid seed dressing ban is likely to have significant impacts on the viability of growing oilseed rape in England particularly where CSFB activity/risk is high. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
(50 reference statements)
2
37
1
Order By: Relevance
“…This is the first study detailing changes in insecticide use in response to the CITF restrictions in maize and sunflower. For OSR, studies in the UK (and one in Germany) also reported a lack of alternative seed treatments and increases in foliar treatments, which we confirm based on our comprehensive dataset on insecticide use over three consecutive growing seasons . An increased reliance on a more limited range of insecticides with the same mechanism of action, such as pyrethroids, may worsen issues associated with insecticide resistance .…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This is the first study detailing changes in insecticide use in response to the CITF restrictions in maize and sunflower. For OSR, studies in the UK (and one in Germany) also reported a lack of alternative seed treatments and increases in foliar treatments, which we confirm based on our comprehensive dataset on insecticide use over three consecutive growing seasons . An increased reliance on a more limited range of insecticides with the same mechanism of action, such as pyrethroids, may worsen issues associated with insecticide resistance .…”
Section: Discussionsupporting
confidence: 72%
“…Another aspect not addressed by our study is temporal pest population dynamics, which could have effects on other farmers and crops as well. Such dynamics, together with potential resistance development, learning by farmers and changing availability of insecticides mean that the pest management changes observed for the first year after the restrictions cannot necessarily be extrapolated to subsequent growing seasons, which require further study …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations